Mixed lubrication of steel by C18 fatty acids revisited. Part I: Toward the formation of carboxylate. (February 2015) - Loehlé, S.; Matta, C.; Minfray, C.; Mogne, T.Le; Iovine, R.; Obara, Y.; Miyamoto, A.; Martin, J.M.
Abstract: The requirements in automotive lubrication impose more complex lubricant formulation. For environmental issues, it is important to reduce additives containing sulfur and phosphorous compounds. We propose to revisit the lubrication of steel by stearic acid with a new approach combining experimental and molecular simulation techniques. The adsorption mechanism of stearic acid on iron oxide surface is investigated by ultra-accelerated quantum chemistry molecular dynamics simulations. Adsorption experiments are performed followed by in-situ XPS and ex-situ PMIRRAS analyses. The adsorption mechanism occurred through the acid group mainly by chemisorption. Friction behavior of stearic acid with iron oxide is studied. Results suggest that the friction process favors the formation of carboxylate function. The low friction behavior seems to be related to the generation of a SAM strongly bonded to the surface. Highlights: We simulate the generation of an adsorbed layer of stearic acid on iron oxide surface by ultra-accelerated quantum chemistry molecular dynamics (UA-QCMD) calculations. In situ adsorption followed by XPS analysis is performed to validate the model. In addition, PM-IRRAS analysis is also performed. The adsorption of stearic acid under self-assembled monolayer (SAM) on iron oxide surface occurred through the acid group, mainly by chemisorptions. Low friction coefficient is reported in presence of stearic acid, which is related to the generation of a SAM strongly bonded to the iron oxide surface. Both UA-QCMD and PM-IRRAS confirmed that the formation of carboxylate is promoted by friction.